The Position of Arbitration in Dispute Resolution of Islamic Financial Institutions - Ni Nyoman Adi Astiti; Ghozali Rahman; Siti Nur Ibtisamah (AL-QARDH, 2021)
Arbitration in Islamic law is known as the term tahkim which comes from Arabic. Arbitration in Islam has been recognized in the Al-Qur’an, Sunnah and Ijmak. In Indonesia, sharia arbitration focuses on the field of muamalah or sharia-based civil law. Sharia arbitration is very relevant in resolving sharia banking disputes. The practice of tahkim has been done by the companions of the Apostle. Thus, the problems that are resolved by arbitration institutions are not against Islamic law, because Islamic law itself recognizes the legality of arbitration as dispute resolution. However, in the formation of an arbitration institution, elements prohibited by religion should not be included and its decisions are also not contradicting religious law. If a case is related to an arbitration institution to settle it, then according to Islamic law the official judicial institution is no longer authorized.